Targeted escape of SARS-CoV-2 in vitro from monoclonal antibody S309, the precursor of sotrovimab - Magnus, Clara Luzia; Hiergeist, Andreas; Schuster, Philipp; Rohrhofer, Anette; Medenbach, Jan; Gessner, André; Peterhoff, David; Schmidt, Barbara (Frontiers in Immunology, 2022)
Class 1 and 2 monoclonal antibodies inhibit SARS-CoV-2 entry by blocking the interaction of the viral receptor-binding domain with angiotensin-converting enzyme 2 (ACE2), while class 3 antibodies target a highly conserved epitope outside the ACE2 binding site. We aimed to investigate the plasticity of the spike protein by propagating wild-type SARS-CoV-2 in the presence of class 3 antibody S309. After 12 weeks, we obtained a viral strain that was completely resistant to inhibition by S309, due to successively evolving amino acid exchanges R346S and P337L located in the paratope of S309. The antibody lost affinity to receptor-binding domains carrying P337L or both amino acid exchanges, while ACE2 binding was not affected. The resistant strain replicated efficiently in human CaCo-2 cells and was more susceptible to inhibition of fusion than the original strain. Overall, SARS-CoV-2 escaped inhibition by class 3 antibody S309 through a slow, but targeted evolution enabling immune escape and altering cell entry. This immune-driven enhancement of infectivity and pathogenicity could play an important role in the future evolution of SARS-CoV-2, which is under increasing immunological pressure from vaccination and previous infections.